(Re)Calling London: The Gender Frame Agenda within NBC's Primetime Broadcast of the 2012 Olympiad. (March 2014) - Billings, Andrew C.; Angelini, James R.; MacArthur, Paul J.; Bissell, Kimberly; Smith, Lauren R.
All sixty-nine hours of National Broadcasting Company's (NBC) 2012 primetime Summer Olympic telecast were analyzed, revealing significant gender trends. For the first time in any scholarly study of NBC's coverage of the games, women athletes received the majority of the clock-time and on-air mentions. However, dialogues surrounding the attributions of success and failure of athletes, as well as depictions of physicality and personality, contained some divergences by gender.